PENGARUH KUALITAS LAYANAN, KUALITAS PRODUK, PROMOSI DAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN KENDARAAN BERMOTOR (Students' Journal of Economic and Management, 2013)
This research is a study to analyze the effect of quality of service, quality of product, promotion and design of the motor vehicle purchase decisions Yamaha Mio J. Object of this study is that consumers who buy Yamaha Mio J on the CV. Motor Ungaran lasting. In this study, researchers used purposive sampling and obtain the sample size of 100 respondents. Data obtained from the questionnaires. Questionnaire data was processed using SPSS. Results of data analysis showed that the research model has a good agreement and all the research hypothesis can be proven. The conclusion drawn is the quality of service, quality of product, promotion and design significantly influence the purchase decision.This study has the limitations of the limited samples of research as one of the principal sources of data, which is limited to consumers who buy vehicles Yamaha Mio J on the CV. Lasting Motor Ungaran, besides the variables used in the study is limited to the variable quality of service, quality of product, promotion and design. There may be other factors that have more influence in determining the customer purchase decision on the CV. Lasting Motor Ungaran, eg price, distribution, places, and others.Keywords: Quality of Service, Quality Products, Promotion, Design and Purchasing Decisions.